The Effectiveness of Repetitive Transcranial Magnetic Stimulation for Post-stroke Dysphagia: A Systematic Review and Meta-Analysis - Wen, Xin; Liu, Zicai; Zhong, Lida; Peng, Yang; Wang, Jing; Liu, Huiyu; Gong, Xiaoqian (Frontiers in Human Neuroscience, 2022)
Background: Repetitive transcranial magnetic stimulation (rTMS) applied to mylohyoid cortical region has positive clinical effects on post-stroke. Therefore, we conducted a meta-analysis to investigate the efficacy of rTMS for the patients with post-stroke dysphagia. Methods: According to PRISMA guidelines，we searched the databases of MEDLINE (PubMed), Cochrane Library，Embase, Web of Science, CNKI, Wangfang from they were established to September 2021. We searched for studies of randomized controlled trials (RCTs) of rTMS for dysphagia after stroke and screened by inclusion and exclusion criteria. Features of RCTs were extracted. The heterogeneity of the trials was measured by I² statistic. Results: In total, 11 RCTs with 463 dysphagia patients fulfilled our inclusion criteria. In our analysis, rTMS demonstrated a great beneficial for post-stroke dysphagia when combined with traditional swallowing exercises. Moreover, greatly significant difference (P=0.008) based on stimulation frequency (high frequency or low frequency) was noted. Additionally, no significant difference (P=0.53) based on stimulation site (affected or unaffected stimulation) was observed. Conclusions: Overall, rTMS can effectively accelerate the improvement of swallowing function in patients with post-stroke swallowing disorder.